Development of a sandwich ELISA for the thrombin light chain identified by serum proteome analysis - Kazuyuki Sogawa; Kana Kobayashi; Shintaro Kikkawa; Shigetsugu Takano; Hideyuki Yoshitomi; Hirotaka Takizawa; Masayuki Ohtsuka; Hiroaki Shimizu; Katsunori Furuhata; Masaru Miyazaki; Osamu Yokosuka; Fumio Nomura (Practical Laboratory Medicine, 2017)
We previously identified novel biomarker candidates in biliary tract cancer (BTC) using serum proteome analysis. Among several candidates, we focused on thrombin light chain which is a 4204 Da peptide as the most promising biomarker for BTC. To move thrombin light chain toward potential diagnostic use, we developed an enzyme immunoassay that enables to measure serum thrombin light chain levels.Both one monoclonal antibody specific to the N-termini and one polyclonal antibody were used to develop a sandwich ELISA for thrombin light chain. The assay was evaluated by comparing the results with those obtained by the ClinProt™ system. Serum samples were obtained from 20 patients with BTC, 20 patients with BBTDs and 20 HVs using the ClinProt™ system and ELISA.The results of the established ELISA showed a positive correlation with the findings by ClinProt™ system (slope=0.3386, intercept=34.901, r2=0.9641). The performance of the ELISA was satisfactory in terms of recovery (97.9–102.5%) and within-run (1.5–4.8%) and between-day (1.9–6.7%) reproducibility. Serum thrombin light chain levels were significantly greater in BTC (176.5±47.2 ng/mL) than in BBTDs (128.6±17.4 ng/mL) and HVs (127.6±16.0 ng/mL) (p<0.001).The sandwich ELISA developed in this study will be useful for validation of the diagnostic significance of serum thrombin light chain levels in various cancers. Keywords: Thrombin light chain, Biliary tract cancer, Sandwich ELISA, Serum biomarker